Kajian Fiqih Muamalah Terhadap Praktik Jual Beli Biji Kopi di Desa Tanjung Kecamatan Pakis Aji Kabupaten Jepara: Study of Fiqh Muamalah on the Practice of Selling and Buying Coffee Beans in Tanjung Village, Pakis Aji District, Jepara Regency - Rofi’ah, Malikatur (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Buying and selling is an activity that is in the circulation of life. The research aims to describe the study of fiqh muamalah on the practice of buying and selling coffee beans in Tanjung Pakis Aji Jepara Village and its contracts. The research method is descriptive qualitative. The first discussion of the sale and purchase carried out includes “permissible” in fiqh law including: (1) Al-'aqidain related to the seller and buyer are adults, of sound mind, and their own will, (2) Al-ma'qud 'alaih related to the sale of coffee is pure, useful, and their own property, (3) Sighat al- 'aqd related to ijab qabul based on willingness and words of mutual consent. The second discussion relates to the salam contract. It appears that the payment is earlier than the delivery of the coffee. The purchase agreement is partly done orally and some buyers write on a piece of paper to avoid doubts. Suggestions include: (1) We should pay attention to buying and selling that is regulated by Islamic law, so that no party to the coffee trading transaction is harmed. (2) The seller and buyer should take notes to avoid misunderstandings and doubts.